Fine‐needle aspiration of metastatic melanoma presenting as bilateral breast cysts. Issue 5 (20th March 2017) - Inouye, Casey M.; Cimino‐Mathews, Ashley; Eisner, David; Rosenthal, Dorothy L.; VandenBussche, Christopher J.
Abstract : Melanoma is the second most common non‐hematopoietic malignancy after carcinomas to metastasize to the breast and often appears as a well‐circumscribed, dense nodule on imaging. Although metastatic lesions presenting as bilateral cysts have been reported, this presentation is not common and may mimic benign breast cysts. We present a challenging case of metastatic melanoma presenting as bilateral breast cysts with spindled cytomorphology in a patient with a history of mammary carcinoma. Discordance between the spindled cytomorphology and the morphology of the core biopsy, which was similar to the patient's primary breast cancer, allowed for entertainment of other tumors and disease processes. Confirmatory immunostaining of the cytology material with HMB‐45 was important to establish the diagnosis of metastatic melanoma. Diagn. Cytopathol. 2017;45:446–451. © 2017 Wiley Periodicals, Inc.